Bufei huoxue capsules in the management of convalescent COVID-19 infection: study protocol for a multicenter, double-blind, and randomized controlled trial. (August 2021) - Chen, Yuqin; He, Wenjun; Lu, Wenju; Xing, Yue; Bai, Jianling; Yu, Hao; Zhou, Jiawei; Liang, Jingyi; Chen, Jiyuan; Hou, Chi; Zhong, Bihua; Wang, Ting; et al.
Up to 30 May 2021, the cumulative number of patients diagnosed with corona virus disease-19 (COVID-19) globally has exceeded 170 million, with more than 152 million patients recovered from COVID-19. However, the long-term effect of the virus infection on the human body's function is unknown for convalescent patients. It was reported that about 63% of COVID-19 patients had observable lung damage on CT scans after being released from the hospital. Bufei Huoxue (BFHX) capsules, including three active ingredients of traditional Chinese herbal medicine, has been used clinically to prevent and treat pulmonary heart diseases with Qi deficiency and blood stasis syndrome. Some small-scale clinical trials have found that BFHX can improve lung ventilation function, reduce blood viscosity, and improve cardiopulmonary function. However, the efficacy and safety of BFHX in the treatment of the recovery phase of COVID-19 are unknown. This study is a multicenter, double-blinded, randomized, controlled trial. Subjects with convalescent COVID-19 were randomized (1:1) into either a BFHX or control group and observed for three months concomitant with receiving routine treatment. The primary efficacy indicators are the evaluation results and changes of the St. George's Respiratory Questionnaire score, Fatigue Assessment Inventory, and 6-min walk distance. Based on the intention-to-treat principle, all randomly assigned participants will be included in the statistical analysis. The last visit's outcomes will be used as the final outcomes for participants who prematurely withdraw from the trial. Per protocol set will pick up from the full analysis set for analysis. Efficacy analysis will be performed on the intention-to-treat datasets and per-protocol datasets. This study and its protocol were approved by the Ethics Committee of our University. Prior to participation, all subjects provided written informed consent. Results will be disseminated at medical conferences and in journal publications. We aimed to determine the efficacy and safety of BFHX for the treatment of the convalescent COVID-19 patients. Trial registration number: ChiCTR2000032573